The history of embalming in the era of anatomists of the XV-XVIII centuries - Chilingaridi Svetlana Ninelievna; Shemyakov Sergey Evgenievich; Milyukov Vladimir Yefimovich; Nikiforova Elena Evgenevna; Sharifova Kheyalya Murshud Kizi; Sharifov Elshan Rovshan Oglu; Nguyen Cao Cuong (International Journal of Human Anatomy, 2023)
A historical review traces embalming practices and their role in anatomical study between the 15th and 18th centuries, connecting technique evolution to scientific milestones and ethics.
Keywords: Embalming